How do Asian American young adults influence the health of family members? Structural equation modeling of age, acculturation, interactivity, and closeness - Shahmir H. Ali; Anika Nayak; Xiang Qi; Supriya Misra; Ralph J. DiClemente (Springer, 2024)
Abstract Family members of Asian Americans (AAs) hold enormous potential as health changemakers to help combat the growing non-communicable disease burden in the community. To inform the development of impactful family-based interventions, there is a need to disentangle the mechanisms behind family influences on health. This study aims to deconstruct how interactivity and closeness mediate the association of age and acculturation with how much AA young adults perceive themselves to influence the health behaviors of family members. 502 AA young adults (48.0% East Asian, 20.9% South Asian, 23.1% Southeast Asian) were recruited in March 2021 to participate in an online survey on family interaction patterns, providing data on 944 unique dyadic family relationships. Associations between age, acculturation, interactivity (shared family activities, living proximity, and interaction frequency), closeness (family connectedness and interaction quality), and family health influence (reflecting influence on diet, exercise, sleep, stress, substance use, and relationship building) were evaluated through structural equation modeling. The final model displayed strong fit (CFI:0.956, RMSEA:0.081, SRMR:0.041), and revealed that an increase in closeness compared to interactivity corresponded with a greater increase in family health influence, with both completely mediating the association between age and family health influence. Acculturation was not associated with closeness, and its effect on family health influence was only partially mediated through interactivity. In subgroup analyses, neither interactivity nor closeness mediated the relationship between age and family health influence among South Asians (unlike East and Southeast Asians). Findings suggest the importance of targeting interactivity and closeness separately when developing AA family-based health interventions, and considering how the age and acculturation profile of AA young adults may shape these dynamics.